The curse of the cheese pyramid - Stilton, Geronimo (New York : Scholastic, 2004)
Geronimo travels to Egypt to interview Professor Alrat Spitfur and learns the secret of the Seven Wonders of the Ancient Mouse World.
"English translation... by Edizioni Piemme S.p.A."--T.p. verso.
G3
Keywords: Mice -- Juvenile fiction; Animals -- Juvenile fiction; Stilton, Geronimo (Fictitious character) -- Juvenile fiction; Mice -- Fiction; Animals -- Fiction; Pyramids -- Fiction; Journalists -- Fiction; Adventure and adventurers -- Fiction; Humorous stories; Egypt -- Fiction